2021
DOI: 10.1124/molpharm.121.000294
|View full text |Cite|
|
Sign up to set email alerts
|

β2-Adrenoceptor Agonists Promote Extracellular Signal-Regulated Kinase 1/2 Dephosphorylation in Human Airway Epithelial Cells by Canonical, cAMP-Driven Signaling Independently of β-Arrestin 2

Abstract: Chronic use of β2-adrenoceptor agonists as a monotherapy in asthma is associated with a loss of disease control and an increased risk of mortality. Herein, we tested the hypothesis that β2adrenoceptor agonists, including formoterol, promote biased, β-arrestin 2 (βArr2)-dependent activation of the mitogen-activated protein (MAP) kinases, ERK1/2, in human airway epithelial cells and, thereby, effect changes in gene expression that could contribute to their adverse clinical outcomes. Three airway epithelial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Previously, we determined by western blotting that βArr2 is the predominant, non‐visual arrestin in BEAS‐2B cells with relatively little βArr1 (Hamed et al, 2021). In that study, we also reported using CRISPR/Cas9 genome editing with different sgRNAs the generation of three BEAS‐2B cell clones deficient in βArr2 (Hamed et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we determined by western blotting that βArr2 is the predominant, non‐visual arrestin in BEAS‐2B cells with relatively little βArr1 (Hamed et al, 2021). In that study, we also reported using CRISPR/Cas9 genome editing with different sgRNAs the generation of three BEAS‐2B cell clones deficient in βArr2 (Hamed et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in a frameshift mutation and the generation of a premature stop codon. BEAS-2B cells deficient in βArr2 were generated as described previously (Hamed et al, 2021).…”
Section: Derivation Of Crispr/cas9 Beas-2b Cell Clones Deficient In P...mentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibition of ERK relieved skin symptoms in a mouse imiquimod-induced model ( Wu et al, 2018 ; Huang X et al, 2019 ). A latest study reported that β 2 -AR agonists promote ERK dephosphorylation in human airway epithelial cells by cAMP-PKA signaling ( Hamed et al, 2021 ), although some earlier studies showed that PKA mediates the switch of coupling of β 2 -AR from Gs to Gi and initiate the activation of ERK pathway ( Daaka et al, 1997 ; Zamah et al, 2002 ; Smith et al, 2021 ). Thus, we examined ERK phosphorylation in psoriasis-like skin lesions.…”
Section: Resultsmentioning
confidence: 99%